Cover Crops for Managing Root-Knot Nematodes - Harsimran K. Gill; Robert McSorley (EDIS)
Root-knot nematodes are widespread and are pests of almost all major crops. Damage can be seen as galls or knot-like swellings produced along plant roots. Cover crops are used to manage nematodes because these microscopic roundworms can move only very short distances on their own and will starve without suitable host plants. This 6-page fact sheet describes several common cover crops that can be used for nematode management. Written by Harsimran K. Gill and Robert McSorley and published by the UF Department of Entomology and Nematology, July 2011.